ASSIGNMENT OF RIGHT COMPENSATION COSTS DETERMINATION ECONOMIC BASE FOR THE LEGAL TRANSACTIONS CONFESSED INVALID - Поздняков, Юрій; Садовенко, Юрій (Socio-economic relations in the digital society, 2019)
In the article it is set mostly influented pricing factors that determine complete or partial property rights cost indexes — assignment of right compensation costs in property/ monetary resources return to parties of legal purchase-sale transactions agreement confessed invalid cases. Th e analysis of the got valued costs index accordance to the fair value concept is done. Th eoretical base of the off ered methodology is certain as the obtained independent estimation basic principles. Th e comparative analysis of estimated intangible asset general and special characteristics, for the cases of mutual unliquidated debts between purchase-sale transaction agreement confessed invalid parties, and debtor account receivable, is considered. By described researches it is shown, that implementation of evaluation works in this class cases is highly complicated by the large variety of possible evaluation situations. Th e variation spectrum of these evaluation situations descriptions demonstrates considerable variation in the wide range of major characteristics, such as: purchase-sale transaction property costs; conditions of property sale; descriptions of the same class property market situation; period of time term that passed from a purchase-sale transaction property agreement conclusion moment to the moment of this agreement invalid confession, and others like that. In the article it is suggested to carry out diff erentiation of all possible this class tasks evaluation situations on the basis of their dichotomy division with the sign of time period duration passed from a purchase-sale transaction property agreement conclusion moment to the moment of this agreement invalid confession court decision. In the article is educed that the major economically-legal consequences of court decision about transaction agreement invalid confession within the limits of it’s interpretation in the modern economical measurements paradigm are the facts of appearance of the mutual unliquidated debts between purchase-sale transaction agreement parties, and also appearance these parties duty on bilateral agreement property restitution. It is well-proven that the date of this mutual debts appearance is chronologically due to the moment of court decision about transaction agreement invalid confession cramps acceptance. But here, in obedience to an actually operating legislative norm, the term of this debt existence follows to deduct from the date of the transaction agreement confessed. The last conclusion is predefi ned by operating legislative norm, in obedience to which the legal «transaction confessed by a court invalid is invalid from the moment due the transaction date». Id est, court law qualifi cation of legal transaction that took place in a past tense is corrected at that rate nowadays court decreets — and the task of appraiser is to obtain and defi ne by calculation economic changes number that took place as a result of this adjustment in nowadays contemporaneity. It is shown that at purchase-sale transaction property agreement subject legal status uncertainty situation presence, in most general case of the evaluation situations investigated class; it is expedient to examine the property rights costs as an intangible asset. On the basis of the got conclusions it is suggested for this class tasks decision to apply methodologies of independent valuation/appraising, which are used for the of costs estimation of the most closely near aft er economic non-material assets valuation/appraising, — namely, account receivable. Th us, as a result of undertaken study and analysis of operating legislative base it is set forth and proved some practical recommendations, especially of independent estimation methodical base choice suitable for the property (property rights) costs calculation obtaining on the legal transactions agreements confessed invalid in the judicial order. Possibility and expediency of interpretation of estimation object, that was transaction agreement subject in such evaluation situations, are shown. So, estimation object is examined as an intangible asset — namely, as a bundle/package of complete or partial property rights, depending on the degree of estimation object legal status uncertainty and the time period duration passed from a purchase-sale transaction property agreement conclusion moment to the moment of this agreement invalid confession court decision.